The Mediating Role of Competence in the Influence of Job Characteristics on Job Satisfaction - Adhika, I Nyoman Resa (Jurnal Manajemen Pelayanan Hotel, 2024)
This study aims to analyze the mediating role of competence in the influence of job characteristics on employee job satisfaction at The Vira Boutique Hotel and Suites Bali. Job characteristics including skill variety, task identity, task significance, autonomy, and feedback are considered as factors that contribute to the development of employee competence, which in turn increases job satisfaction. The sample used in this study was 55 hotel employees. The results showed that job characteristics significantly influenced competence and job satisfaction. Competence also played a significant mediating role in the relationship between job characteristics and job satisfaction.